2014
DOI: 10.1007/978-1-4939-2230-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Protein Synthesis Systems Derived from Cultured Mammalian Cells

Abstract: We present a technology for the production of target proteins using novel cell-free systems derived from cultured human K562 cells and Chinese hamster ovary (CHO) cells. The protocol includes the cultivation of cells, the preparation of translationally active lysates, and the cell-free synthesis of desired proteins. An efficient expression vector based on the internal ribosome entry site (IRES) from the intergenic region (IGR) of the cricket paralysis virus (CrPV) was constructed for both systems. The coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…An insect cell-free system offers core protein glycosylation without the need for supplementing the microsomes in the reaction (Stech et al, 2014;Tarui et al, 2001). Recent studies reported the expression of recombinant erythropoietin using microsomes in CHO cell-free system showing the presence of glycosylated and unglycosylated forms (Brodel et al, 2013(Brodel et al, , 2014(Brodel et al, , 2015. However, the reports have been confined to autoradiography studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An insect cell-free system offers core protein glycosylation without the need for supplementing the microsomes in the reaction (Stech et al, 2014;Tarui et al, 2001). Recent studies reported the expression of recombinant erythropoietin using microsomes in CHO cell-free system showing the presence of glycosylated and unglycosylated forms (Brodel et al, 2013(Brodel et al, , 2014(Brodel et al, , 2015. However, the reports have been confined to autoradiography studies.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators (Table 1) have used the E. coli CFPS, insect CFPS and CHO CFPS systems for the expression of human EPO (Ahn, Choi, & Kim, 2005;Ahn, Hwang, Lee, Choi, & Kim, 2007;Brodel, Sonnabend, & Kubick, 2014;Brodel, Wustenhagen, & Kubick, 2015;Stech et al, 2014). However, no further optimization studies were reported.…”
mentioning
confidence: 99%
“…The translation of hBMP2 is initiated by a 5 -end cap region and that of the EGFP by an IRES sequence. In addition, a linear template for cell-free expression was generated by a two-step PCR procedure, as previously described [29]. pMK-CRPV-Mel-hBMP2 (3.9 kb, Fig.…”
Section: Dna Constructsmentioning
confidence: 99%
“…CHO cell lysate preparation and cell-free protein synthesis were performed as previously described [26,29]. Briefly, cells were suspended in lysis buffer (40 mM HEPES, pH 7.5, 100 mM NaOAc, 4 mM DTT) at approximately 5 × 10 8 cells/mL and syringed through a 20-gauge needle.…”
Section: Cell-free Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation